Endoplasmic reticulum‐resident Rab8A GTPase is involved in phagocytosis in the protozoan parasite Entamoeba histolytica. (4th April 2016) - Hanadate, Yuki; Saito‐Nakano, Yumiko; Nakada‐Tsukui, Kumiko; Nozaki, Tomoyoshi
Summary: Phagocytosis is indispensable for the pathogenesis of the intestinal protozoan parasite Entamoeba histolytica . Here, we showed that in E. histolytica Rab8A, which is generally involved in trafficking from the trans‐Golgi network to the plasma membrane in other organisms but was previously identified in phagosomes of the amoeba in the proteomic analysis, primarily resides in the endoplasmic reticulum (ER) and participates in phagocytosis. We demonstrated that down‐regulation of EhRab8A by small antisense RNA‐mediated transcriptional gene silencing remarkably reduced adherence and phagocytosis of erythrocytes, bacteria and carboxylated latex beads. Surface biotinylation followed by SDS‐PAGE analysis revealed that the surface expression of several proteins presumably involved in target recognition was reduced in the EhRab8A gene‐silenced strain. Further, overexpression of wild‐type EhRab8A augmented phagocytosis, whereas expression of the dominant‐negative form of EhRab8A resulted in reduced phagocytosis. These results indicated that EhRab8A regulates transport of surface receptor(s) for the prey from the ER to the plasma membrane. To our knowledge, this is the first report that the ER‐resident Rab GTPase is involved in phagocytosis through the regulation of trafficking of a surface receptor, supporting a premise of direct involvement of the ER in phagocytosis.